Identification and in silico functional prediction of lineage-specific SNPs distributed in DosR-related proteins and resuscitation-promoting factor proteins of Mycobacterium tuberculosis. Issue 12 (December 2020) - Tantivitayakul, Pornpen; Juthayothin, Tada; Ruangchai, Wuthiwat; Smittipat, Nat; Disratthakit, Areeya; Mahasirimongkol, Surakameth; Tokunaga, Katsushi; Palittapongarnpim, Prasit
Abstract: One-third of the world population is infected by Mycobacterium tuberculosis, which may persist in the latent or dormant state. Bacteria can shift to dormancy when encountering harsh conditions such as low oxygen, nutrient starvation, high acidity and host immune defenses . Genes related to the dormancy survival regulator (DosR) regulon are responsible for the inhibition of aerobic respiration and replication, which is required to enter dormancy. Conversely, resuscitation-promoting factor (rpf) proteins participate in reactivation from dormancy and the development of active tuberculosis (TB). Many DosR regulon and rpf proteins are immunodominant T cell antigens that are highly expressed in latent TB infection. They could serve as TB vaccine candidates and be used for diagnostic development. We explored the genetic polymorphisms of 50 DosR-related genes and 5 rpf genes among 1, 170 previously sequenced clinical M. tuberculosis genomes. Forty-three lineage- or sublineage-specific nonsynonymous single nucleotide polymorphisms (nsSNPs) were identified. Ten nsSNPs were specific to all Mtb isolates belonging to lineage 1 (L1). Two common sublineages, the Beijing family (L2.2) and EAI2 (L1.2.1), differed at as many as 26 lineage- or sublineage-specific SNPs. DosR regulon genes related to membrane proteins and the rpf family possessed mean dN/dS ratios greater than one, suggesting that they are under positive selection. Although the T cell epitope regions of DosR-related and rpf antigens were quite conserved, we found that the epitopes in L1 had higher rates of genetic polymorphisms than the other lineages. Some mutations in immunogenic epitopes of the antigens were specific to particular M. tuberculosis lineages. Therefore, the genetic diversity of the DosR regulon and rpf proteins might impact the adaptation of M. tuberculosis to the dormant state and the immunogenicity of latency antigens, which warrants further investigation. Abstract : Microbiology; Genetics; Molecular biology; Infectious Disease; Lineage-specific SNP; DosR-related proteins; rpf proteins; T cell epitopes; Mycobacterium tuberculosis .